Analyze of Parameter Values of Sasirangan Home Industry Wastewater at Hot and Cold Dyeing - Noraida, Noraida; Khair, Abdul (Medical Laboratory Technology Journal, 2024)
The sasirangan fabric home industry produces wastewater through the hot and cold dyeing process. It is necessary to know the coloring process and wastewater parameter values to design good wastewater treatment. The purpose of the study was to compare the wastewater parameter values including pH, NH3-N, BOD5, COD, TSS, Oil/Fat, Color, Phenol, Temperature, H2S and Crom Total from Sasirangan Home Industry Wastewater at Hot and Cold Dyeing. This type of research is comparative research with static group comparison design. The sample is a portion of wastewater from home industries from in the province of South Kalimantan Indonesia, namely Banjarmasin City, Banjarbaru City, and Banjar Regency. The sampling technique used accidental sampling with a total of 20 samples consisting of 10 samples of the hot dyeing process and 10 samples of the cold dyeing process. Parameters that do not meet the standards in the hot dyeing process are pH, BOD5, COD, TSS, color, and phenol, while in the cold dyeing process are BOD5, COD, TSS, and color. Statistically, there is a significant difference in the parameter values of pH, TSS, color, phenol, and temperature in sasirangan cloth home industry wastewater between the two processes. The results of the research can be used for planning wastewater treatment for the Sasirangan home industry.